Oxytocin can decrease germ cells apoptotic index in testis under acute ischemia reperfusion in a rat model - Rezvaneh Ghasemnezhad; Fahime Mohammadghasemi; Masoumeh Faghani; Mohammad Hadi Bahadori (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2015)
Background: Ischemia reperfusion (IR) is the main pathology of torsion of testis and it is a common urologic emergency. There is some evidence that shows oxytocin (OT) plays role in ischemia reperfusion. Objective: To evaluate this hypothesis that OT can decrease germ cell apoptotic index in testis under acute ischemia reperfusion in a rat model. Materials and Methods: 20 adult rats were randomly divided into four groups: Control, IR, OT and IR+ OT (OTA). Testicular ischemia was achieved by 720° torsion of the left testis for 2 hr. Then, torsion was removed and reperfusion was performed. Immediately after induction of reperfusion 0.03 µg/kg OT were administered intraperitoneally to the IR+ OT. Three hours after surgery left testis was removed and evaluations were made by Johnson's score, ELISA, immunohistochemistry and histomorphometry for study of maturity of spermatogenesis, endocrine profiles, apoptosis and quantitative studies, respectively. Results: The results showed in addition tissue edema and congestion, a significant reduced in Johnson's score were detected in IR group in comparison with controls (p=0.01), and apoptotic index increased significantly (p=0.001). Administration of OT in OT+IR group, increased Johnson's score but it was not statistically significant. Germinal epithelium thickness was increased significantly (p=0.03), although apoptotic index decreased significantly in comparison with the IR group (p=0.04). However there was not significant difference in serum levels of testosterone, FSH and LH in none of groups (p=0.07). Conclusion: These results suggested that OT can decrease apoptotic index and improves complication of acute ischemic reperfusion in testis in a rat model.